OLANZAPINE FOR NAUSEA AND VOMITING IN VARIOUS ETIOLOGIES : A REVIEW - Yulistiani; Kuswandi, Nabila Aulia Yasmin (Brawijaya University, 2023)
Nausea is an unpleasant response followed by the risk of vomiting that results rapid forced ejection of gastric substance from the stomach upwards and out of the mouth. The Gastrointestinal tract, vestibular system, and thalamus are the sites that cause this event. Serotonin type 3 (5-HT3), Mu, neurokinin-1 (NK-1), kappa opioids, dopamine type 2 (D2) are CTZ receptors that cause emesis. 5-HT3 antagonists, antihistamines, and phenothiazines are common antiemetic agents. Olanzapine is an atypical antipsychotic second-generation medication with antiemetic properties. The article review method involves searching the database for various research articles. The activity of olanzapine with several receptors associated with nausea and vomiting suggests that it may have antiemetic activity. Olanzapine inhibits the 5-HT2C receptor, which is located near small intestine enterochromaffin cells and is required for the emetic response. In CINV therapy, research suggests combining olanzapine 10 mg with a 5-HT3 antagonist, NK-1 antagonist, dexamethasone. Low dose olanzapine at 5 mg is used in hyperemesis gravidarum.